Y^4-4y^3+7y^2-6y-2y^3+8y^2-14y+12=
y^4-6y^3+15y^2-20y+12
or
y^3-4y^2+7y-6=y^3-4y^2+4y+3y-6=
y(y^2-4y+4)+3(y-2)=
y(y-2)^2+3(y-2)=(y-2)[y(y-2)+3]=(y-2)(y^2-2y+3)
(y^3-4y^2+7y-6)(y-2)=(y-2)^2(y^2-2y+3)
Answer:
D
Step-by-step explanation:
Area of the square ( 5.1x5.1 ) added to
Area of one triangle ( 0.5x5.1x5.95 ) times 4 (because there are four triangles)
Answer:
y = 2x
Step-by-step explanation:
Answer:
y=x-4 or f(x)=x-4
Step-by-step explanation:
therefore, x=1 ,y=-3; x=2, y=-2 ; etc
The solution to the inequality expression is x ≥ 30
<h3>How to solve the
inequality expression?</h3>
The inequality expression is given as:
8x - 3(2x - 4) ≤ 3(x - 6)
Open the brackets in the above inequality expression
8x - 6x + 12 ≤ 3x - 18
Collect the like terms in the above inequality expression
8x - 6x - 3x ≤ -12 - 18
Evaluate the like terms in the above inequality expression
-x ≤ -30
Divide both sides of the above inequality expression by -1
x ≥ 30
Hence, the solution to the inequality expression is x ≥ 30
Read more about inequality expression at
brainly.com/question/24372553
#SPJ1